Development of a Model-tracing Intelligent Tutor in Diagnostic Pathology - Crowley, Rebecca S. (2001)
We report on the design and development of an intelligent tutoring system in diagnostic pathology. Based on a cognitive model of skill in this domain, the system provides individualized instruction to students. An underlying production-rule system models diagnostic skills as a set of production-rules and domain knowledge as a set of working-memory elements. The model-tracing aspect of the system guides the student to correctly search a slide, identify relevant evidence, and formulate and test hypotheses before making a diagnosis. The system directs student attention, offers hints based on the student's progress through the problem, prevents errors, and provides individualized feedback.